MODEL PENGEMBANGAN KURIKULUM MADRASAH DINIYAH PONDOK PESANTREN - Muhammad Alfian (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
The development of Islamic boarding schools with various types of typologies is the impact of the development of the education system, which certainly requires an analysis of the projections of experts in accordance with their fields, in this case pesantren are required to concoct curriculum, prepare curriculum development strategies and then implement it well, although not all Modern theories have relevance to the world of pesantren on the one hand, and at the same time pesantren also need the concept of implementing a modern curriculum. The problem in this research is how the curriculum development model for pesantren diniyah madrasas. The purpose of this study is to describe the development model This type of research is field research (Field Research), using historical approaches and case studies. The data collection techniques are interviews, observation and documentation, using inductive qualitative data analysis techniques. The results of this study are: First, Islamic boarding schools with early education have implemented curriculum development. The curriculum of the Diniyah Takmiliyah Madrasah is in accordance with the wishes of the organizers with the domination of the kiyai and ustad, and has not made the curriculum guidelines based on Diniyah Takmiliyah implementation guidelines of the Indonesian Ministry of Religion in total, which makes the gap between the ideal curriculum and the actual curriculum affect the implementation of the curriculum as it is, and there is still an ongoing repetition of material between formal and non-formal education. In the theory of Miller-Seller states that development and implementation is by paying attention to the components of curriculum development, determining the steps of curriculum development, so early Islamic boarding schools in Bengkulu do not yet have curriculum documents, but have their own ways in curriculum development namely combination models.